A review of the genus Rickettsia in Central America - Bermúdez Castillero, Sergio Eduardo (2018)
In this paper, we present a historical review of rickettsiosis in Central America and also the most recent findings of Rickettsia in ectoparasites. All countries of Central America have records of rickettsiosis. Regarding the typhus group rickettsioses, there is clinical or serological evidence of Rickettsia prowazekii in Guatemala, Rickettsia typhi in Panama, Guatemala, and Costa Rica and unidentified species of the typhus group in El Salvador. Concerning spotted fever group rickettsiosis, there is serological evidence of infection by Rickettsia akari in Costa Rica and confirmed cases involving Rickettsia rickettsii in Panama and Costa Rica. There are also reports of spotted fever group rickettsiosis in acute patients from Guatemala, Honduras, and Nicaragua. Serological studies in Central America show reactivity of Rickettsia ambyommatis, Rickettsia bellii, Rickettsia felis, Rickettsia rhipicephali, and R. rickettsii in domestic and wild mammals. Eight species of Rickettsia have been detected in ectoparasites from Central America: R. africae (or very similar), R. amblyommatis, R. asembonensis, R. bellii, R. felis, R. parkeri, R. rhipicephali, and R. rickettsii, in addition to undescribed strains such as Atlantic Rainforest, Colombianensi, IbR/CRC, Barva, Aragaoi, and Candidatus “Rickettsia nicoyana;” the latter being the only one associated with Argasidae (Ornithodoros knoxjonesi). R. amblyommatis is the most common species in Central America, seeing as it has been reported in 10 species of ticks and one of fleas in five of the seven countries of the region. In this study, we demonstrate that the genus Rickettsia is widely distributed in Central America and that rickettsiosis could be an underestimated problem in the absence of greater diagnostic efforts in undetermined febrile cases.